2013
DOI: 10.1080/00207543.2012.737952
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic mutual adjustment search for supply chain operations planning co-ordination

Abstract: and decentralized planning systems. Centralized systems can theoretically optimize supply chain performance although its implementation requires a high degree of information exchange among supply chain partners. This leads to difficulties when independent partners do not want to share information. In order to address these difficulties, decentralized systems are designed for supply chains where each member is a separate economic entity that makes its operational decisions independently, yet with some minimal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…In our literature review we bring together two streams of research, which are the one on operations pooling and on distributed decision-making. Various collaborative planning schemes have been introduced in the literature (Fransoo, Wouters, and de Kok 2001;Taghipour and Frayret 2013;Thomas et al 2015;Gansterer and Hartl 2018b;Pan et al 2019). These are referred to as horizontal, if participants act at the same levels in a market (Cruijssen, Dullaert, and Fleuren 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In our literature review we bring together two streams of research, which are the one on operations pooling and on distributed decision-making. Various collaborative planning schemes have been introduced in the literature (Fransoo, Wouters, and de Kok 2001;Taghipour and Frayret 2013;Thomas et al 2015;Gansterer and Hartl 2018b;Pan et al 2019). These are referred to as horizontal, if participants act at the same levels in a market (Cruijssen, Dullaert, and Fleuren 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is observed that with the support of a large number of documents, scholars have done a great deal of work on the applicability of the contract. The details from very simple models to very complex models are different, and coordination among multiple actors at different levels of the supply chain can be achieved through contract execution ( [42], [43]). The analysis of the contract implementation between supply chain members should pay more and more attention in theory and practice.…”
Section: Future Researchmentioning
confidence: 99%
“…At the same time, centralized planning cannot be reasonably implemented as an efficient coordination of the IPDS in SCs with different manufacturers’ objectives. Indeed, such planning requires an unrealistic level of information exchange, which is ultimately a deterrent to such a practice (Taghipour and Frayret [ 27 ]). Furthermore, a decision that is optimal with respect to both stages together (production and distribution) might not be an optimal decision for each stage individually, especially when suppliers, manufacturers, distributors, and customers may have different conflict goals.…”
Section: Literature Reviewmentioning
confidence: 99%